Optimising the refrigeration and cooling system of a platinum mine - Buys, Johan Leon (My University, 2014)
The platinum mining sector of South Africa (SA) has been hit by the combined impacts of falling Platinum Group Metals (PGM) prices, labour strikes and escalating production cost. The main contributor pertaining to production cost rises is the increasing electricity tariffs. In order for mines in the platinum sector to remain competitive, they need to reduce the energy consumption of electrical intensive mining equipment. Platinum mines in SA require large surface refrigeration systems due to the high underground Virgin Rock Temperatures (VRT) gradients. Due to these high demands, refrigeration and cooling systems are identified as one of the most intensive electricity consumers in the mining process. The need, therefore, exists to investigate optimisation strategies that can improve the Energy Efficiency (EE) of platinum mines refrigeration and cooling system. The availability of Eskom’s Energy Efficiency Demand-Side Management (EEDSM) incentives provides the opportunity to optimise the electricity consumption with cost-effective strategies. The incentive will not only reduce the demand of electricity, but also assist platinum mines on managing their production cost increases more cost-effectively. In this study, optimisation strategies were investigated that can be implemented on platinum mines surface refrigeration and cooling system, along with underground water reticulation systems. It was shown that through optimising both the service deliveries supply and demand, larger saving can be realised. Optimising strategies were identified to address possible inefficiencies in the refrigeration and cooling system of platinum mines. The strategies entail water flow control to match the cooling supply with the demand by means of implementing Variable Speed Drives (VSDs), and equipment that will reduce the underground chilled water wastage of secondary spot coolers. After implementation of proposed optimisation strategies on a case study, an average annual power saving of R12.5-million was realised, without affecting the service deliveries thereof. Potential results indicated that an additional annual saving of R0.8-million could be realised by implementing the proposed optimising equipment on the underground spot coolers.
MIng (Mechanical Engineering), North-West University, Potchefstroom Campus, 2015